2017
DOI: 10.1016/j.ygyno.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, open-label, phase 2 study of the IDO1 inhibitor epacadostat (INCB024360) versus tamoxifen as therapy for biochemically recurrent (CA-125 relapse)–only epithelial ovarian cancer, primary peritoneal carcinoma, or fallopian tube cancer

Abstract: This first report of immunotherapy evaluation in biochemical-only relapse ovarian cancer and of IDO1 inhibitor monotherapy in ovarian cancer found no significant difference in efficacy between epacadostat and tamoxifen. Epacadostat was generally well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 33 publications
0
59
0
Order By: Relevance
“…No objective responses were detected, although stable disease for ≥16 weeks was observed in 7/52 patients (106). A randomized Phase 2 study compared epacadostat versus tamoxifen treatment in 42 patients with biochemically recurrent-only epithelial ovarian cancer, primary peritoneal carcinoma or fallopian tube cancer, where epacadostat was found to be well tolerated but showed no difference in efficacy (107). …”
Section: Discovery and Preclinical Development Of Ido1 Inhibitorsmentioning
confidence: 99%
“…No objective responses were detected, although stable disease for ≥16 weeks was observed in 7/52 patients (106). A randomized Phase 2 study compared epacadostat versus tamoxifen treatment in 42 patients with biochemically recurrent-only epithelial ovarian cancer, primary peritoneal carcinoma or fallopian tube cancer, where epacadostat was found to be well tolerated but showed no difference in efficacy (107). …”
Section: Discovery and Preclinical Development Of Ido1 Inhibitorsmentioning
confidence: 99%
“…In human patients, epacadostat monotherapy was not effective (163,164), while combined administration with PD-1 or cytotoxin T-lymphocyte-associated protein 4 (CTLA-4) inhibitors showed promising clinical activity in phase I/II studies (165)(166)(167)(168). Unfortunately, a recent trial with combined administration of epacadostat with pembrolizumab found no superiority over pembrolizumab alone (169).…”
Section: Immune Tolerance Related To Indoleamine 23-dioxygenase 1 Acmentioning
confidence: 99%
“…The National Comprehensive Cancer Network (NCCN) guidelines for OC suggest that biochemical recurrent patients may: 1) enroll in a clinical trial; 2) delay treatment until clinical relapse; 3) receive immediate platinum-based recurrence therapy; or 4) undergo best supportive care (25). Thus, several studies aimed to investigate low-toxicity agents to delay the appearance of measurable disease in these patients (26). However, no e cacy agent was con rmed until now.…”
Section: Discussionmentioning
confidence: 99%